(untitled) (Academicia Globe: Inderscience Research, 2022)
Through the cluster approach to the organization of laboratory work in chemistry in general secondary schools; we explain the main essence of laboratory work through the method of interconnection of the given topics, creating a basis for students to understand the following topics. At the same time, even in schools where the raw material base (reagents) is not enough, we will be able to explain several topics in relation to each other through the chemicals that are present in our daily lives. For example, crystalline soda, which is familiar through the subject of carbon, and mineral fertilizers on the subject of nitrogen and phosphorus, which are easy for us to find in the economy and do not require additional equipment in the reaction process, as well as in the minds of students. It provides a demonstration view of the process rather than a virtual laboratory view. As a result, through practice, students will be able to master and analyze more than one topic, and will be able to analyze chemical reagents through sensory receptors when they encounter them in their daily lives. At the same time, the clustering method of laboratory training does not require the phrase "jet shortage or lack of equipment", and it is easy to integrate and master several topics.